2020
DOI: 10.1515/jpm-2019-0474
|View full text |Cite
|
Sign up to set email alerts
|

Estimated fetal weight and severe neonatal outcomes in preterm prelabor rupture of membranes

Abstract: AbstractObjectivesOur aim was to study the association of clinical variables obtainable before delivery for severe neonatal outcomes (SNO) and develop a clinical tool to calculate the prediction probability of SNO in preterm prelabor rupture of membranes (PPROM).Methods Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A recent study for prediction of SNO conducted by Jose R. Duncan et al [ 15 ] reported that estimated fetal weight could be used as a clinical toll to calculate the prediction probability of SNO in PPROM. In their model, several variables available before delivery such as gestational age, diabetes mellitus, fetal growth restriction and the appearance of clinical chorioamnionitis et al were enrolled in their model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study for prediction of SNO conducted by Jose R. Duncan et al [ 15 ] reported that estimated fetal weight could be used as a clinical toll to calculate the prediction probability of SNO in PPROM. In their model, several variables available before delivery such as gestational age, diabetes mellitus, fetal growth restriction and the appearance of clinical chorioamnionitis et al were enrolled in their model.…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies developed graphical tools or model to predict survival or survival without severe morbidities in preterm infants [ 12 14 ]. To facilitate prediction in PROM pregnancies, Jose R. Ducan et al used clinical variables obtainable before delivery for severe neonatal outcomes and found estimated fetal weight showed significant effect on the prediction probability of the SNO [ 15 ]. Physicians and parents sometimes need to make critical decisions about neonatal care with short- and long-term implications on infant’s health and families.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the evaluated adverse neonatal outcomes in our secondary outcomes have been previously validated and are known to cause severe morbidity and mortality in premature infants [37,39]. Lastly, both charts studied were derived from the Hadlock formula, and the same has been validated in our PPROM population [36], and the EFW in this population has been shown to be a significant predictor of adverse perinatal outcomes [40].…”
Section: Discussionmentioning
confidence: 99%